De l’eau pour les défunts. Les hydries à décor peint en contexte funéraire attique de l’âge du Fer à l’époque archaïque - Alexandra Alexandridou (Pallas, 2014)
The present paper attempts to explore the role of the fine decorated hydriai within the Attic necropoleis from the last decades of the eighth until the first quarters of the sixth century BC. The shape was favoured by the Late Geometric IIb and Early Protoattic workshops before disappearing from the Attic repertoire after the second quarter of the seventh century. The context, iconography and characteristics of these hydriai suggest that they can be considered ritual vessels bearing a particular symbolism, when found in funerary contexts. The examination of the shape in connection with the early loutrophoroi-hydriai offers valuable insights into its significance and its allusion to the nuptial bath. The early sixth century saw the reappearance of the painted hydriai in the Attic burial grounds and in particular inside the offering trenches. By that time, it seems that although they retained their nuptial connotations, their funerary role had been modified as hey addressed to different deceased.